2018
DOI: 10.1155/2018/6845026
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Tin Oxide Hollow Nanoflowers Interfering with Quorum Sensing-Regulated Functions and Bacterial Biofilms

Abstract: Monophasic tin dioxide nanoflowers (TONFs) assembled by rod-like nanostructures were prepared by coprecipitation method using tin chloride and ammonia precipitators, as the starting materials, without using any surfactants or templates. The structural, compositional, optical, and morphological properties of TONFs were investigated by XRD, FT-IR, UV-vis, SEM-EDX, and TEM techniques. Synthesized TONFs demonstrated inhibition of quorum sensing- (QS-) regulated virulence in pathogens, viz., Chromobacterium violace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 58 publications
5
17
0
Order By: Relevance
“…We recorded a significant reduction in biofilm biomass upon treatment with the core and Core/shell NSs. Our study is in accordance with previous reports that showed the reduction of biofilms in P. aeruginosa PAO1 by nanoparticles of zinc oxide 14,51 , tin oxide 52 and iron oxides 53 , silica nanoparticles 54 antimicrobials like doxycycline and ceftazidime 29,55 .
Figure 5Anti-biofilm activity of NSs. ( a ) Percent inhibition of biofilm formation of PAO1 by sub-MICs of core and core/shell NSs using microtitre plate assay.
…”
Section: Resultssupporting
confidence: 92%
“…We recorded a significant reduction in biofilm biomass upon treatment with the core and Core/shell NSs. Our study is in accordance with previous reports that showed the reduction of biofilms in P. aeruginosa PAO1 by nanoparticles of zinc oxide 14,51 , tin oxide 52 and iron oxides 53 , silica nanoparticles 54 antimicrobials like doxycycline and ceftazidime 29,55 .
Figure 5Anti-biofilm activity of NSs. ( a ) Percent inhibition of biofilm formation of PAO1 by sub-MICs of core and core/shell NSs using microtitre plate assay.
…”
Section: Resultssupporting
confidence: 92%
“…27 Moreover, nanoparticles of iron oxide, tin oxide, gold, copper and organosilane have also been shown to inhibit biolm of L. monocytogenes. [42][43][44][45][46] This is probably the rst report on the inhibition of biolm formation in Listeria species by green synthesized AgNPs.…”
Section: Effect On Biolm Formationmentioning
confidence: 74%
“…Exopolysaccharides (EPS) are an important constituent of the bacterial biofilm as they have a vital role in the maintenance of the 3D biofilm architecture and providing resistance against the action of antimicrobials and immune responses [ 48 ]. Several studies have highlighted that interference with EPS production leads to disturbed biofilm architecture and eventually reduces the development of resistance against antimicrobials [ 49 , 50 , 51 ]. In light of this, TA-AuNPs were evaluated for their ability to inhibit EPS production in S. marcescens as well as L. monocytogenes .…”
Section: Resultsmentioning
confidence: 99%